Strategi Pemasaran Produk Minuman Serai (Cymbopogon Citratus) Herbal di CV. Nadis Herbal, Badung, Bali - Evarini, Ni Kadek; Wiranatha, Anak Agung Putu Agung Suryawan; Wrasiati, Luh Putu (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2025)
CV. Nadis Herbal is a company that produces serai (Cymbopogon citratus) herbal drink products in the Badung area. This research aims to analyze the conditions of internal factors (strengths and weaknesses) and external factors (opportunities and threats) of herbal drink products by CV. Nadis Herbal, to formulate alternative strategies that can be used in herbal drink products by CV. Nadis Herbal and to determine priorty alternatives to increase sales at CV. Nadis Herbal. The business development strategy uses SWOT analysis (Strength, Weakness, Opportunities and Threats) and is supported by quantitative analysis using the IFE, EFE, IE and QSPM matrices. The number of respondents in this study was 6 experts. Based on the research that has been carried out, the SWOT analysis formed the IFE and EFE matrices with scores of 2.73 and 2.60, indicating that the herbal drink company is in quadrant cell V (Hold and Maintain) in the IE matrix, then the SWOT matrix obtained six alternative strategies which were analyzed using the QSPM matrix as a decision. formulation of appropriate marketing strategies. So that a priority strategy is obtained based on the analysis, namely that Nadis Herbal can take advantage of its strengths in making high-quality herbal drink products to take advantage of the trend of healthy and natural drinks in increasing market potential with a total TAS score of 6.70.